Imaginarios sobre la seguridad ciudadana y la delincuencia construidos a partir de los medios de comunicación TC Televisión y Teleamazonas - Ulrich Vivas, Ana Gabriela (2014)
The social imaginary are mental constructions that are reaffirmed through the culture and common behaviors in a society. As such, they tend to move in every moment of everyday life, reflected in the way we see the realities and build images on certain specific facts involved and influence our development and interaction with others.